PENGARUH UKURAN PERUSAHAAN, MODAL KERJA, DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA SUB SEKTOR INDUSTRI BARANG KONSUMSI (MAKANAN & MINUMAN) YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Dina Andriani; Seniwati Sembiring; Aria Masdiana Pasaribu (Fakultas Ekonomi Universitas Al-Azhar Medan, 2023)
This study aims to determine the effect of firm size, working capital, and sales growth on consumer goods (food and beverage) companies listed on the Indonesia Stock Exchange in 2018-2020. The population in this study was 29 companies, and the sample obtained for three years is ten companies, so 30 observation data was received. The sampling technique used is multiple linear regression analysis. The results of this study conclude that partially, the firm size variable affects profitability, while the working capital and sales growth variables do not affect profitability. Simultaneously, Company Size, Working Capital, and Sales Growth Affect Profitability